2019
DOI: 10.1186/s40360-019-0363-1
|View full text |Cite
|
Sign up to set email alerts
|

Antihistamine effects and safety of fexofenadine: a systematic review and Meta-analysis of randomized controlled trials

Abstract: BackgroundAs a new generation antihistamine, fexofenadine has been widely used in allergic diseases. However, there is still a lack of collective evidence regarding the antihistamine effects and safety profiles of fexofenadine relative to other antihistamine drugs and placebo. Therefore, we aimed to systematically evaluate the antihistamine effects and safety of fexofenadine.MethodsAn electronic literature search of randomized controlled trials (RCTs) was performed using Embase, Cochrane and PubMed from establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 68 publications
1
17
0
3
Order By: Relevance
“…They could also prevent airway inflammation and hyperreactivity which is caused by allergens [14]. The known inhibitors of histamine-1 receptors are levocetirizine [15], desloratadine [16], and fexofenadine [17]. Cysteinyl leukotriene receptor-1 is the receptor of leukotriene.…”
Section: Introductionmentioning
confidence: 99%
“…They could also prevent airway inflammation and hyperreactivity which is caused by allergens [14]. The known inhibitors of histamine-1 receptors are levocetirizine [15], desloratadine [16], and fexofenadine [17]. Cysteinyl leukotriene receptor-1 is the receptor of leukotriene.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with first-generation antihistamines, systematic reviews of randomized controlled trials have found newer antihistamines to be safer (e.g., 4% sedation v. 28%), 2 – 4 longer lasting (12–24 h v. 4–6 h dosing) and faster acting (50 v. 80 min). 1 The World Health Organization replaced chlorpheniramine with loratadine on its essential medicines list in 2013 for these reasons (see Table 1 and Appendix 1, available at www.cmaj.ca/lookup/doi/10.1503/cmaj.201959/tab-related-content for preferred antihistamines).…”
Section: Newer Antihistamines Are Safer As Affordable and As Efficacmentioning
confidence: 99%
“…Как следует из полученных результатов, открываемость внесенных добавок фексофенадина гидрохлорида находилась в интервале от 95 до 105%, аммония глицирризината -от 85 до 106,25% при величине RSD не более ±3,74% и ±7,84% соответственно, что соответствует предъявляемым требованиям 8 [30].…”
Section: результаты и обсуждение разработка методики количественного определения фексофенадина гидрохлорида и аммония глицирризината при unclassified
“…Фексофенадин имеет благоприятный профиль лекарственной безопасности, превосходящий таковой у антигистаминных препаратов первого поколения. Отсутствие седативного эффекта позволяет использовать препарат различным группам населения, в том числе в рабочее время, так как не нарушается концентрация внимания, моторные и когнитивные функции [8][9][10][11][12].…”
Section: Introductionunclassified